Handbook of international law - Aust, Anthony (Cambridge University Press, 2005)
A concise and accessible account of international law by an experienced practitioner. This book explains how states and international organisations, especially the United Nations, make and use international law. The nature of international law and its fundamental concepts and principles are clearly described.